Effect of Clinically Competent Nurses Services on Safety and Patients' Satisfaction in an Emergency Department - Reza Negarandeh; Shadan Pedram Razi; Mohammad Khosravinezhad (Tehran University of Medical Sciences, 2013)
Background & Aim: Access to quality care is important in delivering health services. Patientschr('39') safety and satisfaction are indicators of quality of care evaluation. Competent nurses may deliver quality care . This study aimed to investigate the impact of using competent nurses on patients' safety and satisfaction .   Methods & Materials: In t his interventional study with non-equivalent control group, we selected 120 patients admitted to the emergency department of Imam Khomeini hospital in 2012 using convenience sampling method . Nursing care for the experimental group (n=40 ) was provided by nurses who had high competency scores and in the control group ( n=80), nursing care was provided by usual emergency department nurses . Data were collected using the patient satisfaction with nursing care quality (PSNCQ), and patient safety inventory. Data were analyzed in the SPSS v.16 using descriptive and inferential statistics . The significance level for all statistical tests was considered at P<0.05 .   Results: Mean age of the intervention and control groups were 48.1 ( ±12.5) and 40.5 ( ±16.7), respectively (P<0.018). There was a significant difference between the two groups in terms of employment (P<0.009). The two groups were similar in terms of other variables such as gender, marital status, level of education, having health insurance , and the reasons for seeking admission . The results showed that there were significant differences between the two groups in patients' safety and satisfaction with nursing care (P<0.001). Regression test was used to eliminate the effects of age and job satisfaction the results showed effect of intervention on the patients' safety and satisfaction with nursing care .   Conclusion: These findings indicated that using competent nurses in providing nursing care promotes patients' safety and satisfaction with nursing care. Training nurses focusing on the level of competency is required in scheduling, staffing, and implementing nursing care to enhance safety, patient satisfaction , and quality of care.